Redefinição das áreas de risco para a raiva bovina no Estado de Goiás - El-Aouar, Ludmyla Veiga (2019)
Rabies is an acute encephalomyelitis that affects humans and animals, caused by a virus usually transmitted by the saliva of an infected animal and whose vaccination is the most effective method for its control. Since 2002, the Ministry of Agriculture, Livestock and Supply has established standards for herbivore rabies control and has defined the receptivity and vulnerability criteria for determining areas of low and high risk for the disease. In Goiás, rabies vaccination has been mandatory since 2005.The objective of this study was to evaluate the strategy of vaccination against rabies in the state of Goiás from 2000 to 2018 and to propose a new classification of risk areas. Data analysis used reports of laboratory tests of cattle performed at LABVET / AGRODEFESA within the time series. Pearson's correlationtest was used to evaluate the relationship between the number of tests performed and the number of confirmed diagnosis; and the chi-square test was applied to compare infection rates among the administrative regions of AGRODEFESA in the state. The temporal distribution of positive diagnosis of rabies in cattle was represented in trend tables and estimates, and the structured information in the LibreOffice 6.0.3 program and for parametric and nonparametric statistics, resources from the Bioestat 5.0 statistical package were used. A total of 4736 laboratory tests for bovine rabies from 237 sampled municipalities were analyzed. The positive exam rate was 30% (n = 1468). The trend curve showed a significant decrease in rabies cases from 2005. There were significant differences in the diagnosis of rabies between regionals (p <0.05%) and the high correlation between number of samples analyzed and number of rabies. positive diagnoses, suggesting that the infection rate approached reality. Thirty municipalities 12% (30/273) were considered priority for vaccination, eighty-eight 37% (88/237) were considered strategic and one hundred twenty-eight 54% (128/237) as surveillance areas. Herbivore rabies is controlled in Goiás, vaccination is efficient for disease control, infection rate during the study period was 30%, environmental and management differences influenced the distribution of rabies among regions of the state.